Oral fenofibrate for hyperbilirubinemia in term neonates: A single-blind randomized controlled trial - Seyed Hossein Saadat; Rakhshaneh Goodarzi; Babak Gharaei (Journal of Clinical and Translational Science, 2023)
Abstract